Monitoring of Songbird Trades in Jambi, Indonesia. Issue 1 (March 2021) - Yohanna,; Irham, M; Kurniawan, P T
Abstract: Birds keeping, especially songbirds, has been considered as one of the major drivers that lead to species extinction in Indonesia. The demand for songbirds either for songbird's competition or to be enjoyed at home is considerably high, especially in Java. As the native Javan population has been depleted due to habitat conversion and excessive trapping, the supply of songbirds is provided by other islands in Indonesia such as Sumatera and Kalimantan. We conducted long term monitoring of songbird's trade on Jambi. Data on bird's trade was obtained by examining the transaction records from wholesalers from the period of 2016 – 2020. The results showed that there were shifting in species target especially after 2018 due to implementation of new regulation on protected species. However, the total number remains high. The trade comparison for the same period between trade records in 2016 and 2020 demonstrated the reduction in the number of species from around 32 species to 25 species, however, the total volume of traded birds is higher in 2020 which is 20.600 compare to 7.198 during the first sixth months. Considering the pandemic situation, the songbirds trade activities is seemingly not affected especially for the distribution chain from hunter to wholesalers.